Pengaruh Gaya Eksplorasi Dan Gaya Komando Terhadap Keterampilan dasar bolavoli (Studi Ekperimen di SMA Bukit Barisan) - marta ibnu andi; syafruddin syafruddin; barlianeri eri (Universitas Negeri Padang, 2019)
This study aimedat observing the effect of eksploration style and command styletoward volleyball basic skills achievement. Type of the research wasquasi-experimental(Quasy experiment). The population of this study are high school students of Bukit Barisan class X and XI who follow extracurricular activities of volleyball at least eighty student, while the sample in this study is 20 male students using total sampling technique. The instrument used in this study was a basic bolavoli skill test. Data were analyzed by using t-test (dependent sample and Independent sample) The results ofdata analysisshow that:(1) There are influences eksploration style which significantly to the volleyball basic skills in Students Senior High School Bukit Barisan be obtained the value of t count = 5,61 > t table = 2,26, (2) There are influences command style which significantly to the volleyball basic skills in Students Senior High School Bukit Barisan be obtained the value of t count = 5,93 > t table = 2,26,(3) Eksploration style is more better than series of command style to the volleyball basic skills in Students Senior High School Bukit Barisan be obtained the value of t count = 1,99 > t table = 1,76. The usage exploration method is better than command methode.